Simplification of the Prony Brake Dynamometer System Using Brake Caliper Load - Tjandra, Suhatati; Suhartono, Andri; Salim Suswanto, Tonny (International Journal of Science, Technology & Management, 2023)
The torque of the DC motor needs to be known to determine the maximum load that can be exerted at a given speed. Torque measurement can be done with a dynamometer. The dynamometer uses the Prony Brake type, which uses the principle of frictional force to provide a load on the motor. The application of frictional force uses brake capillary load to produce a dynamometer with the Prony Brake type that is simple in manufacture and testing but reliable and accurate in making measurements. In the Prony Brake dynamometer, there are usually two pieces of wood used as a link between the motor and the torque arm; at the end of the torque arm, there is a ballast whose ballast value is multiplied by the length of the arm to produce the torque value of the DC motor. The results of the trials that have been carried out are that the reading results of RPM sensors, weight sensors, and voltage sensors have a deviation of less than 2%, and the current sensor readings have a deviation of less than 5%. The Prony Brake dynamometer that has been made can read the maximum torque value with a deviation of about 2% from the existing data.